Media Development Interactive Learning Based Articulate Storyline Materials Movement Systems on Humans Class XI High School - Raisa Novianti; Noorhidayati Noorhidayati; Bunda Halang (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2023)
The development of learning media that can be an option so that it can support the times is an interactive learning media based on Articulate Storyline. Effective and interesting interactive learning media, especially for the concept of the human motion system which is classified as complex, can help students achieve the expected learning objectives. This study aims to describe the needs of teachers and student needs, validity, and practicality of the results of the development of interactive learning media on human motion system material. This research is a research and development (R&D) with the 4D model (Thiagarajan et al., 1974). Data collection techniques used instruments of teacher needs and learner needs, validity, and practicality. The research subjects were 3 (three) experts consisting of Biology Education lecturers and one partner teacher and tested at SMA Negeri 9 Banjarmasin Class XI MIPA as many as 12 (twelve) students. The test results show the need to develop interactive learning media on the material of the human motion system, very valid in the validity test, and very practical in the practicality test. This shows that the results of the development of interactive learning media on the material of the human motion system are valid and practical. This interactive media can be used by students anytime and anywhere using devices.